The Eucharistic Feast of Creation - Gatta, John (Anglican theological review, 2023)
The Eucharist, a gospel sacrament and central feature of life in the Christian church, also bears considerable relevance for growing concerns about the “green” complexion of contemporary faith. Yet traditional forms of eucharistic liturgy may not seem initially to address these concerns satisfactorily. What, then, to do? One approach involves pursuing new, experimental alternatives to existing liturgical forms. Such innovations are unlikely, however, to inspire those not yet disposed to welcome them. This paper aims instead to highlight those less-noticed features of classic eucharistic liturgy, both within and beyond the Episcopal Church, that already embody a vital, sacramental vision of engagement with the fullness of God’s creation. In this light, the eucharistic feast enacts not only the believer’s communion with God in Christ, but also the inherently ecological principle of interchange among human worshippers and with every other member of God’s created order.